2009
DOI: 10.1213/ane.0b013e3181bbc401
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Micropore Membrane Inlet Mass Spectrometry–Derived Pulmonary Shunt Measurement with Riley Shunt in a Porcine Model

Abstract: Shunt derived from MMIMS inert gas retention data correlated well with R-S during breathing of oxygen. Shunt as derived by MMIMS was generally less than R-S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…In future, animal experiments in this field may again use highfrequency PaO2 measurements. Event gated (inspiratory and expiratory) multiple inert gas elimination technique may differentiate shunt, dead space, and V/Q distribution during parts of the respiratory cycle [16][17].…”
Section: Discussionmentioning
confidence: 99%
“…In future, animal experiments in this field may again use highfrequency PaO2 measurements. Event gated (inspiratory and expiratory) multiple inert gas elimination technique may differentiate shunt, dead space, and V/Q distribution during parts of the respiratory cycle [16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The MMIMS technology is still being evaluated in on-going studies. In a prior study, the MMIMS-MIGET derived shunt fraction was shown to be highly correlated to the conventionally calculated shunt [19]. The ultrafast paO 2 measurement was previously applied and described in detail by several experimental studies [11,17,18,22,30,34].…”
Section: Discussionmentioning
confidence: 99%
“…An additional shunt calculation from blood gas samples was performed by a previously described and porcine-specific algorithm [19]. A normal saline solution containing the six inert gases, sulphur hexafluoride, krypton, desflurane, enflurane, diethyl ether and acetone, was prepared by a senior chemist (BD).…”
Section: Methodsmentioning
confidence: 99%
“…The FiO 2 was therefore set at 1.0. A previously validated, porcine‐specific algorithm was applied . Body temperature was measured by a rectal probe and normothermia was maintained by body surface warming.…”
Section: Methodsmentioning
confidence: 99%